Prevalence and treatment follow-up of drug-resistant extra-pulmonary tuberculosis in rural communities in Narshingdi, Bangladesh - Afroz, Hafsa; Ali, Md. Azhar; ., Md. Fakruddin; ., Kamrunnahar; Datta, Suvamoy (International Journal of Advances in Medicine, 2017)
Tuberculosis is a chronic communicable disease. Infections are initially asymptomatic and latent but eventually progresses to active disease, which, if left untreated, may have ≥50% mortality. In 2011, an anti-tuberculosis drug resistance survey in Narsingdi, Bangladesh enrolled both new and retreatment patients. In the study, a number of villages were randomly selected and 152 extra pulmonary tuberculosis (EPTB) patients were identified. All the patients received treatment with standardized first-line drug (FLD) regimens and were investigated to document treatment efficiency. Among the patients, 34 were reported in lower income, 112 in medium income and only 06 in higher income group. Farmers (16.4%) in low income group, and female housewives (41.4%) in medium income group were mostly infected. Silicosis and malnutrition were assumed responsible for high EPTB cases in farmers and housewives respectively. The working youth groups (25-34) were found most vulnerable. Extra pulmonary TB sites of infection was found pleural TB 29.6% patients, glands TB 24.3% patients, abdominal TB 21.0% patients, spinal TV 19.7% patients, tubercular meningitis 436% patients & tubercular pericarditis 0.65% patient. Multi-drug resistant (MDR) EPTB was detected in both new and retreatment patients. Patients with MDR-EPTB who had been declared cured with first-line anti-TB treatment had a high rate of TB recurrence and death. The rate of TB recurrence and death was high four years after MDR-TB patients were judged to have been cured. PTB patients in Bangladesh had high recurrence and death rates even after treatment with standardized FLD regimens, reinforcing the need for early survey, diagnosis and treatment, including assessment of treatment outcomes.